Robotic Surgery in Obstructive Sleep Apnea-Hypopnoea Syndrome - Standyło, Arkadiusz; Obuchowska, Aleksandra; Wójcik, Justyna; Ozga, Alicja; Obuchowska, Karolina; Trojanowski, Piotr (Journal of Education, Health and Sport, 2020)
Obstructive sleep apnoea-hypopnoea (OSAH) syndrome is a sleep disorder characterised by pauses in breathing (apnoea) or periods of reduced breathing (hypopnoea) during sleep. It results in cerebral hypoxia and a disturbed sleep pattern. The gold standard treatment for OSA is continuous positive airway pressure (CPAP). However, significant number of patients are not able to tolerate this device and approximately 50% of patients report inability to achieve long term usage to CPAP. Robotic surgery is an emerging technique for sleep surgery. TORS is an alternative treatment for OSA for patients who have failed CPAP treatment or conventional non-robotic sleep surgery. This technology is assisted by remote-controlled miniaturized surgical instruments and magnified visualization with a high-definition three-dimensional camera. Tongue base reduction (TBR) refers to the primary focus of this targeted surgery for obstructive sleep apnea (OSA). TORS approach for OSA may include 2 different surgical steps frequently combined in the same procedures according to the patient’s features: tongue base reduction and supraglottoplasty (SGP). In the light of the present results and of the literature, TORS tongue-base reduction appears to be effective. With the improved visualization and precise tissue removal provided by robotic surgery, TORS may become more widespread in the treatment of OSA in the coming years. There was an improvement in objective and subjective sleep measures. The comparison among pre-operative and post-operative parameters showed a significant decreasing in post-operative AHI, ESS and an increasing of the lowest SpO2 value.